Application of reflectance confocal microscopy in the diagnosis of pemphigus vulgaris and pemphigus foliaceus - Kurzeja, Marta (Dermatology Review/Przegląd Dermatologiczny, 2022)
Reflectance confocal microscopy is a non-invasive diagnostic method that enables real-time visualization of tissues in near-histological resolution. Pemphigus is a chronic autoimmune skin disease in which intra-epidermal blisters are formed as a result of acantholysis, i.e., loss of connection between epidermal cells. A systematic review of the literature on the use of reflectance confocal microscopy in the diagnosis of pemphigus has been carried out in this paper. Reflectance confocal microscopy enables identification of intra-epidermal acantholytic blisters in patients with pemphigus vulgaris and pemphigus foliaceus. The method also enables to identify the localization of blisters – the spinous layer in pemphigus vulgaris, and in the granular layer in pemphigus foliaceus. Thus, reflectance confocal microscopy may allow establishing non-invasively an initial diagnosis of pemphigus and differentiating pemphigus vulgaris from pemphigus foliaceus.